Pengaruh Kecerdasan Emosional Terhadap Pemahaman Akuntansi Dilihat dari Perspektif Gender - Lauw Tjun Tjun; Santy Setiawan; Sinta Setiana (Universitas Kristen Maranatha, 2009)
Intelectual quotient is not a dominant factor in one’s success. Neither in business social life, there use many clever scholars and during their study in university, they’re always be top students, but when they go to work they become their classmates subordinates which havea barely enough academic achievement. A success of life is more determined by Emotional Quotient, which have many aspects link to personality. This research takes on accountancy student population. In the final phase which take 120 unit subject. The method taking of this sample is nonprobability sampling. The data analysis in this research uses a simple linier regression statistic test tools. Base on this test, the account understanding of woman is greater than account understanding of man. Keywords: Emotional Quotient, account understanding